On changes in Rural China: The Rise of Agrarian Capitalism and Dissolution of the Peasantry in Contemporary China - ZHANG, Forrest (Institutional Knowledge at Singapore Management University, 2008)
For decades, Mr. Hong and his family have toiled the ground of Dounan Village, an area of Yunnan Province that became well-known throughout China for the quality of its fresh vegetables. While Hong and his neighbors have, since the early 1980s, concentrated on the small plot of land that the state allocated to them, in recent years, Dounan village has begun producing vegetables in large enough scale to market to distant, wealthy coastal areas, bringing new-found prosperity to the area. After gaining experience producing vegetables both on the plot that the government allocated to his family, and on his neighbors’ plots, where he worked as a temporary hired hand, Hong soon attained sufficient skill and capital to allow him to rent the land held by other households. In this way, Hong increased production, renting at his peak between 10 and 20 mu of land closer to Kunming, the provincial capital city. The Hong family held so much land in this way that they could not provide sufficient labor to manage it. So they in turn were compelled to hire informal, temporary workers, primarily migrants from poor, remote counties in Yunnan province. By expanding beyond subsistence agriculture and using land and labor controlled by those outside his household, the Hong family is no longer a part of the Chinese peasantry. Instead, they have joined the ranks of millions of rural residents participating in rural China’s newest revolution – agrarian capitalism and de-peasantization.